Sumbangan Fundamentalisme pada Tindak Terorisme - Rosmaria Syafariyah Widjajanti (Refleksi: Jurnal Kajian Agama dan Filsafat, 2007)
One form of the prevalent social phenomenon in recent times is fundamentalism. This article explores another form of fundamentalism that gives rise to radicalism, and even terrorism, which has been commonly associated with religion, hence termed religious fundamentalism. In Islam, fundamentalism is not purely a religious phenomenon but more of a social phenomenon taking on religious dimensions. Fundamentalism refers to religious movements that act radically to achieve their goals, claiming the authenticity of religious teachings. Accusing fundamentalists as the instigators of violence is unfair if we only blame religious fundamentalism; modernity also plays a role in the violence in the world. Both religious fundamentalism and modernity contribute to nurturing acts of violence. The main cause that spawns fundamentalism is social change.